Centralized Communication of Blood Culture Results Leveraging Antimicrobial Stewardship and Rapid Diagnostics. (15th July 2019) - Shemanski, Shelby; Bennett, Nicholas; Essmyer, Cynthia; Kennedy, Kevin; Buchanan, Donna M; Warnes, Andrew; Boyd, Sarah
Abstract: Objective: This study aimed to determine if integrating antimicrobial stewardship program (ASP) personnel with rapid diagnostic testing resulted in improved outcomes for patients with positive blood cultures. Method: Beginning in 2016, Saint Luke's Health System (SLHS) implemented a new process where all positive blood cultures were communicated to ASP personnel or SLHS pharmacy staff. Pharmacists then became responsible for interpreting results, assessing patient specific information, and subsequently relaying culture and treatment information to providers. This was a multisite, pre-post, quasi-experimental study (Pre: August to December 2014; Post: August to December 2016). Patients 18 years of age and older with a positive blood culture during admission were included (2014, n = 218; 2016, n = 286). Coprimary outcomes of time to optimal and appropriate therapy were determined from time of culture positivity via gram stain. Secondary outcomes focused on clinical, process, and fiscal endpoints. A pre-post intervention physician survey was conducted to assess the impact on antimicrobial decision making and perceived effect on patient outcomes. Results: There was no difference in time to appropriate therapy groups ( P = .079). Time to optimal therapy was 9.2 hours shorter in 2016 ( P = .004). Provider surveys indicated the process improved communication among clinicians and facilitated a shared decision-making process with a perceived improvement in patient care. Conclusions: An ASP-led blood culture communication process for patients with positive blood cultures was shown to improve time to optimal therapy, support physicians in their decision making on critical lab data, and improve the care for hospitalized patients. Abstract : Integration of antimicrobial stewardship personnel plus rapid identification testing was associated with reduced time to optimal therapy, increased collaboration between clinical staff, and improved care for hospitalized patients with positive blood cultures.